2019
DOI: 10.1002/pmic.201900064
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Comparison of the Bacterial Response to Allicin Reveals Species‐Specific Defense Strategies

Abstract: Allicin, a broad‐spectrum antimicrobial agent from garlic, disrupts thiol and redox homeostasis, proteostasis, and cell membrane integrity. Since medicine demands antimicrobials with so far unexploited mechanisms, allicin is a promising lead structure. While progress is being made in unraveling its mode of action, little is known on bacterial adaptation strategies. Some isolates of Pseudomonas aeruginosa and Escherichia coli withstand exposure to high allicin concentrations due to as yet unknown mechanisms. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 113 publications
(202 reference statements)
0
14
0
Order By: Relevance
“…The garlic defense substance allicin is a potent thiol reagent which targets the cellular redox buffer glutathione and accessible -SH groups in proteins (Borlinghaus et al, 2014). Allicin has been shown to S-thioallylate several cysteine-containing proteins in bacteria (Müller et al, 2016;Chi et al, 2019;Loi et al, 2019;Wüllner et al, 2019) and humans (Gruhlke et al, 2019) and has been described as a redox toxin (Gruhlke et al, 2010). S-thioallylation by allicin is reversible and sublethal doses suppress bacterial multiplication for a period of time, the length of which is dose-dependent, before growth resumes (Müller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The garlic defense substance allicin is a potent thiol reagent which targets the cellular redox buffer glutathione and accessible -SH groups in proteins (Borlinghaus et al, 2014). Allicin has been shown to S-thioallylate several cysteine-containing proteins in bacteria (Müller et al, 2016;Chi et al, 2019;Loi et al, 2019;Wüllner et al, 2019) and humans (Gruhlke et al, 2019) and has been described as a redox toxin (Gruhlke et al, 2010). S-thioallylation by allicin is reversible and sublethal doses suppress bacterial multiplication for a period of time, the length of which is dose-dependent, before growth resumes (Müller et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There are indications that the allicin target and cellular redox buffer glutathione (GSH) plays a central role in enabling cells to resist the effects of allicin (Gruhlke et al, 2010(Gruhlke et al, , 2017Leontiev et al, 2018). Allicin reversibly Sthioallylates a range of proteins in bacteria and human cells which can lead to loss of function of essential enzymes (Müller et al, 2016;Chi et al, 2019;Gruhlke et al, 2019;Loi et al, 2019;Wüllner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This was demonstrated with an rpoH mutant which was not able to induce the heat shock response, and unlike the wild type was unable to recover from allicin treatment [31]. Additionally, allicin also induced oxidative stress response genes controlled by the OxyR and PerR regulons, e.g., katA, ahpCF, and thioredoxins in B. subtilis, E. coli, and S. aureus [31,59,60,78].…”
Section: Transcriptomic and Proteomic Studies 31 Effects Of Allicinmentioning
confidence: 97%
“…Likewise, the CtsR and HrcA controlled regulons encoding Clp proteases and DnaK/GroESL chaperones were highly induced in the transcriptomes of B. subtilis and S. aureus [59,60]. Similarly, oxidative unfolding of proteins by allicin was countered by the induction of amino acid biosynthesis genes, ribosomal proteins, and translation factors in several bacteria tested [31,59,60,78,79]. It was shown that the ability to induce the heat shock response in E. coli was essential to overcome the effects of allicin stress.…”
Section: Transcriptomic and Proteomic Studies 31 Effects Of Allicinmentioning
confidence: 99%
“…These proteins reflect the acute stress response of the bacterial cells to the given stress condition and are indicative of the antibiotic mechanism of action. A reference compendium with protein expression profiles of over 100 antimicrobial compounds has been established to aid mode of action analysis of new drug candidates (Bandow et al, 2003;Wenzel et al, , 2012Wenzel et al, , 2013Wenzel et al, , 2014Wenzel et al, , 2015bRaatschen et al, 2013;Stepanek et al, 2016a,b;Müller et al, 2016b;Scheinpflug et al, 2017;Saising et al, 2018;Meier et al, 2019;Wüllner et al, 2019). Radioactive 2D-PAGE should not be confused with two-dimensional difference gel electrophoresis (2D-DIGE), which also compares protein expression profiles by densitometric quantification against a control sample, but is a fluorescent sample multiplexing and not a metabolic labeling technique (Minden, 2012).…”
Section: Proteomic Profilingmentioning
confidence: 99%